Jika x = 2+akar 3 dan y = 3- akar 2 maka x² + y² – 2xy =…

Posted on

Jika x = 2+akar 3 dan y = 3- akar 2 maka x² + y² – 2xy =…

Jawaban Terkonfirmasi

X = 2 + sqrt{3}
y = 3 – sqrt{2}
x^{2} + y^{2} – 2xy = (2 + sqrt{3})^{2} + (3 - sqrt{2})^{2} – 2((2 + sqrt{3}) x (3 – sqrt{2})) = (4 + 4sqrt{3} + 3) + (9 – 6sqrt{2} + 2) – 2(6 – 2sqrt{2} + 3sqrt{3}sqrt{6}) = 18 + 4sqrt{3} – 6sqrt{2} – 12 + 4sqrt{2} – 6sqrt{3} + 2sqrt{6} = 6 – 2sqrt{3} – 2sqrt{2} + 2sqrt{6}

X^2+y^2-2xy=(x-y)(x-y)=(2+akar3-(3-akar 2))^2=(-1+akar3+akar2)^2 hasilnya adalah 6+2(-akar2-akar3+akar6)